Twórczy klimat organizacyjny uniwersytetu - szanse, bariery i dobre praktyki = Creative organizational climate of the university: opportunities, barriers, and good practices - Fordymacka-Król, Izabela (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to present conditions conducive to creativity and innovation in the academic environment through an analysis of the university`s organizational culture. Drawing on a review of the relevant literature, the study identifies mechanisms that support the development of creative potential, including autonomy, trust, openness to error, and a sense of community.
Keywords: klimat organizacyjny; kreatywność; innowacyjność; punktoza; uniwersytet; organizational climate; creativity; innovation; punctosis; university